Relationship between high-density lipoprotein cholesterol levels and nutritional risk screening-assessment-intervention: a multicenter cross-sectional study - Li, Qian; Zhu, Hong; Ma, Xianghua; Zhao, Yan (Frontiers in Nutrition, 2025)
BackgroundGlobally, there is limited literature exploring the relationship between nutritional risk screening, nutritional assessment, nutritional intervention, and HDL-C levels. This study analyzes the relationship between HDL-C levels, nutritional risk screening, assessment, and intervention among newly admitted patients in Jiangsu Province.MethodsBetween October 2020 and June 2021, this study randomly selected 23 hospitals from 12 cities in Jiangsu Province using a stratified cluster sampling method. For nutritional assessment, the study used NRS2002 for risk screening.Results4,190 patients were assessed, revealing a low HDL-C prevalence rate of 30.7%. The prevalence exhibited an “N” shaped distribution with age. The prevalence of low HDL-C among patients assessed at nutritional risk was 34.6%, 1.228 times higher than that of patients without nutritional risk. In terms of nutritional assessment, patients with constipation, severe infection, chronic kidney disease, fever, high CRP, and hypoalbuminemia significantly increased risks of low HDL-C by 1.432, 2.496, 1.543, 3.056, 1.794, and 2.703 times, respectively. Patients with a history of esophageal stricture, malignant tumors, and closed head injuries reduced the risks of low HDL-C by 60.9, 23.3, and 78.8%, respectively. Additionally, patients with nausea and vomiting, pancreatic insufficiency, severe infection, fever, and hypoalbuminemia decreased HDL-C levels by 0.156 mmol/L, 1.465 mmol/L, 0.403 mmol/L, 0.301 mmol/L, and 0.250 mmol/L, respectively. Regarding nutritional intervention, compared to patients who did not receive intervention, those receiving parenteral nutrition significantly lowered HDL-C levels at 1.014 mmol/L, with an increased risk of low HDL-C by 2.048 times. All Ps <0.05.ConclusionNutritional risk, nausea and vomiting, constipation, pancreatic insufficiency, severe infection, chronic kidney disease, fever, high CRP, hypoalbuminemia, and receiving parenteral nutrition are associated with lower HDL-C levels in patients. A history of esophageal stricture, malignant tumors, and closed head injury is associated with higher HDL-C levels in patients.